Social Media and the Fragmentation of Religious Authority among Muslims in Contemporary Indonesia - Hannan, Abd; Mursyidi, Ach Fatayillah (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This study examines the massive use of social media, its role, and its influence on splitting religious authority among internal Muslims in contemporary Indonesia. There are two research questions raised in this study: how is the existence and reality of the popularity of Indonesian Muslims amid the rapid development of social media? How does religious authority within Indonesian Muslims experience fragmentation and the massive use of social media? This study is a netnographic research based on qualitative research. Two types and sources of data are used: primary data in the form of text, visual videos, and images obtained from several social media, especially Instagram and YouTube. In addition, there is also secondary data in the form of statistical data and literature. After analysing field data based on the perspective of Max Weber’s authority theory, this study found that the massive use of social media among Indonesian Muslims today has triggered the birth of various new religious realities, one of which is the division of religious authority. In Indonesia, this fragmentation is marked by the weakening of the existence and influence of earlier Islamic clergy groups and, simultaneously, the emergence of contemporary clergy members with stronger allure and influence. The latter are popular as millennial ustadz, have a populist style, and are known to be quite active in campaigning for religious activities on online-based social media channels.